Analysis of the incidence of children in social isolation during the period of COVID-19 - E. I. Aksenova; A. M. Podchernina; Ya. O. Kachkurkina; M. O. Bocharova; T. Yu. Kurakina (Здоровье мегаполиса)
Introduction. Children's health is an important integral indicator and criterion for the socio-economic wellbeing of society and the state, and is also included in the system of global indicators for achieving the goals in the field of sustainable development of countries. In terms of statistical research and forecasting in health care, children's health indicators can be assessed as the most stable and reliably reflecting the actual situation. The article contains information that allows one to form an idea of the health status of children of various age groups in Moscow in conditions of social isolation and distance learning during the COVID-19 period.Purpose of the study. To identify the main trends in the level of general morbidity among children aged 0-17 in Moscow during the COVID-19 pandemic, both in general and by age groups. Assess how the lockdown associated with the coronavirus outbreak has affected the health of children.Materials and methods. The review used population data, as well as data from federal statistical observation form No. 12 “Information on the number of diseases registered in patients living in the service area of a medical organization” for 2016–2020. Morbidity was analyzed for age groups 0-4 years, 5-9 years, 10-14 years, 15-17 years per 100,000 of the corresponding population.Results and discussion. In 2020, the overall level of child morbidity in the capital amounted to 189.1 thousand cases per 100,000 children, a decrease of 15.6% compared to 2019, in general, for the period from 2016 to 2020 – by 18.6 %.An analysis of the incidence of children showed that in 2020, the conditions of temporary isolation and a decrease in contacts during the COVID-19 pandemic led to a decrease in the registration of a number of diseases: SARS, acute bronchitis, acute conjunctivitis and diseases of the digestive system, as well as a decrease in childhood injuries in all age groups.A characteristic feature for children of all ages was the decrease in the overall incidence in 2020, however, it is worth noting the different rates of decline in indicators for individual classes of diseases depending on age.